Preparation of Pinoresinol and Dehydrodiconiferyl Alcohol from Eucommiae Cortex Extract by Fermentation with Traditional Mucor - Wenyi Jiang; Zhengyou He; Ruijiao Yao; Zhiyang Chen; Xia Zeng; Miao Zheng; Jing Wang; Jia Li; Yong Jiang (Molecules)
Eucommiae Cortex (EC) is frequently used alone or in combination with other active ingredients to treat a range of illnesses. An efficient technical instrument for changing cheap or plentiful organic chemicals into rare or costly counterparts is biotransformation. It combines EC with biotransformation techniques with the aim of producing some novel active ingredients, using different strains of bacteria that were introduced to biotransform EC in an aseptic environment. The high-quality strains were screened for identification after the fermentation broth was found using HPLC, and the primary unidentified chemicals were separated and purified in order to be structurally identified. Strain 1 was identified as Aspergillus niger and strain 2 as Actinomucor elegans; the main transformation product A was identified as pinoresinol (Pin) and B as dehydrodiconiferyl alcohol (DA). The biotransformation of EC utilizing Aspergillus niger and Actinomucor elegans is reported for the first time in this study’s conclusion, resulting in the production of Pin and DA.